Project-Based Learning. A literture review. Working paper - Condliffe, Barbara; Quint, Janet; Visher, Mary; Bangser, Michael; Drohojowska, Sonia; Saco, Larissa; Nelson, Elizabeth (MDRC, 2017)
Examining the scholarly literature published since a seminal review in 2000, this working paper discusses the principles that underlie project-based learning, how it has been used in K-12 settings, the challenges teachers have confronted in implementing it, and what is known about its effectiveness in improving students’ learning outcomes.